High Prevalence of Human Antibodies to Recombinant Duffy Binding-Like α Domains of the Plasmodium falciparum-Infected Erythrocyte Membrane Protein 1 in Semi-Immune Adults Compared to That in Nonimmune Children - Oguariri, Raphael M. (American Society for Microbiology, 2001)
We used a panel of nine fusion proteins that contain different Duffy binding-like α (DBL-α) domains of Plasmodium falciparum-infected erythrocyte membrane protein 1 to assess the levels of antibody activity in serum samples obtained from semi-immune or nonimmune individuals from Lambaréné, Gabon. Recognition was measured in terms of either the prevalence or the magnitude of the response. A strong correlation between the immune status of the patients and reactivity with recombinant proteins was observed, which was interpreted as a reflection of the number of infections acquired over time. The antibody responses were predominantly directed toward variable epitopes of the DBL-α domain. Antibody responses could be reduced by preincubation of the sera with various fusion proteins. A portion of individuals who exhibited high-level responses to all fusion proteins also had antibodies which recognized conserved epitopes. The possibility that a synergizing effect of anti-DBL-α domain antibodies could support chemotherapy is discussed.